Setting the stage for equity-sensitive monitoring of the maternal and child health Millennium Development Goals - Meg E Wirth; Deborah Balk; Enrique Delamonica; Adam Storeygard; Emma Sacks; Alberto Minujin (The World Health Organization, 2006)
OBJECTIVE: This analysis seeks to set the stage for equity-sensitive monitoring of the health-related Millennium Development Goals (MDGs). METHODS: We use data from international household-level surveys (Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys (MICS)) to demonstrate that establishing an equity baseline is necessary and feasible, even in low-income and data-poor countries. We assess data from six countries using 11 health indicators and six social stratifiers. Simple bivariate stratification is complemented by simultaneous stratification to expose the compound effect of multiple forms of vulnerability. FINDINGS: The data reveal that inequities are complex and interactive: inferences cannot be drawn about the nature or extent of inequities in health outcomes from a single stratifier or indicator. CONCLUSION: The MDGs and other development initiatives must become more comprehensive and explicit in their analysis and tracking of inequities. The design of policies to narrow health gaps must take into account country-specific inequities.